The influence of selected factors on perceived enjoyment of the online learning experience: lessons for post-COVID-19 classrooms - van der Walt, Freda; Nkoyi, Anele; Thithi, Mpho (Frontiers in Education, 2024)
Since digital transformation has become a priority in the higher education landscape, it is unlikely that higher education institutions will return to traditional face-to-face teaching and learning. Many higher education institutions have adopted a hybrid approach to teaching and learning in a post-Covid-19 setting. This unplanned forced change has raised concerns about the quality of online teaching and learning, as well as issues related to the student experience thereof. Therefore, it is necessary to consider possible factors that may influence students’ perceived enjoyment of the online teaching and learning experience. To date, very few studies have considered the antecedents of perceived enjoyment of online teaching and learning. The purpose of this paper was to determine the influence of selected factors of online teaching and learning on the perceived enjoyment of students. Quantitative data was collected, and the final sample consisted of 501 students enrolled at higher education institutions. The findings showed that cognitive benefits, perceived usefulness and perceived ease of use are statistically significantly correlated with students’ perceived enjoyment of the online learning experience. The current study contributes to existing knowledge regarding the intention of continued use of online teaching and learning. The findings of this study are also practically relevant for enhancing students’ online learning experiences in a post-Covid-19 setting.